Muscle Dysmorphia: A Comparison Between Competitive Bodybuilders and Fitness Practitioners - Cella, Stefania; Iannaccone, Mara; Cotrufo, Paolo (Journal of Nutritional Therapeutics, 2012)
Objective: The primary aim of this study was to investigate the features of Muscle Dysmorphia and other body image-related concerns in a sample of competitive male bodybuilders. Method: We screened 217 male athletes, 119 bodybuilders and 98 fitness practitioners, recruited in 12 gymnasiums in Southern Italy, by means of an ad hoc socio-demographic schedule, the Muscle Dysmorphia Inventory (MDI) and the Muscle Appearance Satisfaction Scale (MASS). Results: Twenty one of the bodybuilders (17.6%) show high levels of preoccupation and dissatisfaction with their muscularity, 45.4% (N=54) a marked dependence on bodybuilding; 35.3% (N=42) follow a high-protein diet and 35.3% (N=42) used vitamin supplements to improve their weightlifting performances and favor post-training physical recovery. In addition, forty-three (36.1%) also report use of substance while nine subjects (7.6%) declare to avoid situations in which their body might be seen or manifest high levels of distress when this happens. The ANCOVA (Exercise Frequency per Week as a covariate) results indicate that bodybuilders, compared to fitness practitioners, report significant elevations in all measures. Moreover, considering only the bodybuilders sample, who report a regular use of substance scored higher in Dietary Behavior, Body size-symmetry, Physique Protection, Supplement Use MDI scales and on Body building Dependence, Muscle Checking and Injury MASS subscales. Discussion: Our findings seem to suggest that the practice of the bodybuilding is associated to the proposed criteria of muscle dysmorphia if compared with regular fitness practice. In particular, we found that a regular use of substance was associated with greater dissatisfaction with muscularity.